SURGICAL TACTICS IN PATIENTS WITH PENETRATING THORACIC INJURIES (World Science, 2021)
To date, the basis of surgical tactics for chest injuries is the primary surgical treatment of the wound and drainage of the pleural cavity with dynamic monitoring and determination of indications for surgery, based on the amount of blood released by drainage, without any attempts to actively verify the nature of injuries.Treatment of patients on the basis of the so-called "individual approach" and active-waiting tactics, taking into account clinical, radiological and laboratory data, mainly meets the recommendations of the middle of the last century.From the standpoint of evidence-based medicine, thoracoscopy is the most effective method of topical diagnosis of traumatic hemothorax. Videothoracoscopic technologies significantly reduce the incidence of purulent intrapulmonary and pleural complications in penetrating lung injuries. Undoubted advantages of thoracoscopy are: full-fledged revision; accurate diagnosis, which eliminates doubts about the diagnosis and waiting period; determination of indications for drainage, operative thoracoscopy or thoracotomy.